Sistema de aquisição de dados com baixo custo para medições de nível em um reservatório líquido - Melo, Mateus Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
The work in question is a bibliographic survey for the construction of a data acquisition system through a microcontroller, the system has as a measure of a liquid reservoir and the transmission of this data in question through the use of the Internet, What is planned is that data transmission is done through an ethernet protector, the application is finalized using an Android platform to capture and back up data, the development of projects to facilitate the monitoring of measurements of levels.
Monografia
Keywords: Arduíno; Ethernet shield; Appinventor2; Medição de nível; Sensor ultrassom; Arduíno; Ethernet shield; Appinventor2; Level measurement; Ultrasonic sensor; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA